Hypermetabolic Conversion of Plant Oil into Water: Endothermic Biochemical Process Stimulated by Juvenile Hormone in the European Firebug, Pyrrhocoris apterus L - Sláma, Karel; Lukáš, Jan (International journal of insect science, 2016)
The physiological and biochemical mechanisms that enable insects to feed on dry food to secure enough water for larval growth were investigated. The study was carried out with a plethora of physiological methods, ranging from the simple volumetric determination of O2 consumption and water intake to more advanced methods such as scanning microrespirography and thermovision imaging of insect's body temperature. The experiments were done on the European firebug, Pyrrhocoris apterus, which feeds exclusively on dry linden seeds. In order to survive, it needs to drink water or suck a sap from plants occasionally. It was found that the young larval instars compensate the occasional water deficiency by the increased production of metabolic water. The juvenile hormone (JH)-dependent production of metabolic water, which was previously found in other species consuming dry food, was achieved in P. apterus by total metabolic combustion of the dietary lipid (neutral seed oil). The water-producing, hypermetabolic larvae were heated from inside by endothermic energy released from the uncoupling of oxidation from oxidative phosphorylation. The "warm", hypermetabolic larvae burning the dietary oil into CO2 and water showed the increased rates of respiratory metabolism. Microrespirographic recording of these larvae revealed the ratio of the respiratory quotient (RQ, CO2/O2) of 0.7, which indicated the breakdown of a pure triglyceride. The warm hypermetabolic larvae could be easily spotted and distinguished from the "cold" larvae on the screen of a thermovision camera. The last instar larvae lacking the JH were always only cold. They metabolized a carbohydrate substrate exclusively (RQ = 1.0), while the dietary lipid was stored in the fat body. In comparison with the hypermetabolic larvae of some other species fed on dry food, which exhibited the highest rates of O2 consumption ever recorded in a living organism (10-20 mL O2/g per hour), the metabolic difference between the warm and cold larvae of P. apterus was only some 30% (not a reported 10-fold difference), which was presumably due to their ability to drink. We conclude that a very important, though still largely neglected, epigenetic biochemical role of insect JH depends on switchover between the utilization of dietary lipid (+JH; production of metabolic water) and carbohydrate (-JH; lipid storage in the fat body). The hypermetabolic water supply in insects fed on dry food, which is associated with enormous rates of O2 consumption, liberates endothermic energy that heats the body and potentially influences the insect thermoregulation. A possibility that the JH-dependent lipolytic hormone stimulates the total metabolic breakdown of nutritional lipids may be absolutely different from the currently known adipokinetic peptides that have been emphasized.
Keywords: JH; endothermic energy; hypermetabolism; Pyrrhocoris apterus; O2 consumption; juvenile hormone; O2); “warm” and “cold” larvae; respiratory quotient (CO2; uncoupling of oxidation